Research on rational development mode of gas cap marginal water reservoir. Issue 1 (1st October 2022) - Peng, Xuefei; Liu, Rumin; Liu, Haitao; Cai, Yina; Xiao, Sa
Abstract : In this paper, based on the 3D physical simulation experiment of gas cap marginal water reservoirs, a reasonable development method for gas cap marginal water reservoirs is studied. The results show that the ultimate recovery rate of exhausted development is 32.24%, and that of flooding water flooding development is 51.17%, which is 18.93% higher than that of exhausted development. In different permeability layers, there is an amount of residual oil, which is distributed in the oil ring and gas cap. At the same time, the injection time and productivity of flooding water flooding were compared and analyzed by numerical simulation. The one-year recovery rate of exhausted development is the highest, and when the injection ratio is 1.2, the recovery rate is the highest. The research in this paper is of great significance to the formulation of production parameters and the implementation of later reformation measures for the depleted gas cap marginal water reservoirs.